Crowdfunding-Based Fiduciary Warrant in Providing Capital Loans for Small and Medium Enterprises - Ninis Nugraheni (Hasanuddin Law Review, 2020)
Small and Medium Enterprises (SMEs) are organized through people's creativity in developing human and natural resources. However, investment challenges often affect their implementation and production processes, necessitating solutions, such as capital loans from banks and other entities. Crowdfunding is an online loaning service that provides easily accessible loans to SME startups, though a warrant to protect creditors from losing money to ingenuine people is necessary. Therefore, this study examines the appropriateness of a fiduciary warrant as a SMEs collateral object. When fiduciary is used as a loan warrant, debtors are allowed to use collateral objects in their production processes. To make a fiduciary warrant effective, legal protection is required. This study used juridical-normative that relied on legal norms in legislation and court verdicts dealing with societal organizational issues. The results showed that crowdfunding-based credit is an alternative with more straightforward procedures compared to conventional entities.